1994
DOI: 10.1088/0953-4075/27/17/006
|View full text |Cite
|
Sign up to set email alerts
|

An electron momentum spectroscopy investigation of the 4d core states of xenon

Abstract: We repon results for the first electron momentum specmcopy (EMS) investigation into the 4d5/2,3/2 core states of xenon. Experimental binding energy spedra were measured over the momentum range from 0.3 to 1.9 au with the derived 4d m s s section demonstrating the superiority of a distoed wave Eom approximation (DWBA) calculdion over the companding plane wave Eom a p p r o x i d o n (PWBA) calculation. The present result also indicated that the xenon Hamee-Fock (w) wavefunction may be inadequate, in that in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 13 publications
4
26
0
Order By: Relevance
“…On the other hand, the discrepancy in the lower momentum region for both peaks was reduced as the impact energy increased from 600 eV to 1500 eV. Considering the similar phenomenon which has been observed in the atomic d orbitals and some molecular orbitals [24][25][26][27][28][29][30], such as ethylene [29] and oxygen [30] before, the most likely explanation is the distorted wave effects. The distorted wave effects will be reduced as the impact energies of electrons increase because the incoming electron and outgoing electrons will be less influenced by the residual ion's potential.…”
Section: Resultssupporting
confidence: 56%
“…On the other hand, the discrepancy in the lower momentum region for both peaks was reduced as the impact energy increased from 600 eV to 1500 eV. Considering the similar phenomenon which has been observed in the atomic d orbitals and some molecular orbitals [24][25][26][27][28][29][30], such as ethylene [29] and oxygen [30] before, the most likely explanation is the distorted wave effects. The distorted wave effects will be reduced as the impact energies of electrons increase because the incoming electron and outgoing electrons will be less influenced by the residual ion's potential.…”
Section: Resultssupporting
confidence: 56%
“…All in all, the experimental frontier momentum profile of W(CO) 6 seems thus far from being fully converging when E 0 increases from 1.2 to 2.4 keV. Note also that DWIA calculations indicate that, instead of vanishing as it should by virtue of symmetry constraints, the low momentum ''turn-up'' in the (e, 2e) ionization cross-sections for the 3d level of an atomic target like Ti still remains very prominent even at E 0 = 2.4 keV [44,46]. Electron impact energies of the order of 10 keV or more might therefore be necessary for ensuring the convergence of the momentum profiles of W(CO) 6 , Cr(CO) 6 , and Mo(CO) 6 to the high energy limit [102], at which the plane wave impulse approximation becomes valid.…”
Section: Resultsmentioning
confidence: 97%
“…This was expected, since the same symmetry constraints apply in Hartree-Fock and Density Functional Theories. By analogy with EMS experiments on atomic targets and calculations employing the Distorted Wave Impulse Approximation (DWIA [1][2][3]) of the Xe 4d, Cr 3d, Ti 3d and Mo 4d (e, 2e) ionization cross-sections [46], it was tentatively concluded [43,44] that these discrepancies between theory and experiment are due to a breakdown of the plane wave impulse approximation and distorted wave effects in the continuum, which are known indeed nowadays [47] to be particularly significant when the ionized molecular orbital has a d-type topology (i.e., two perpendicular nodal planes).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies of atomic targets 36 have convincingly shown that such effects in d orbitals are due to breakdown of the plane wave impulse approximation ͑PWIA͒ caused by significant low momentum components near the nucleus which can occur in orbitals of grads symmetry for lу2. Distorted wave calculations 36 have predicted that such effects will diminish with increase of impact energy above the commonly used value of 1200 eV and that they will become negligible above a few keV. Unfortunately, at present, DWIA calculations are possible only for atoms but not for molecules due to the multicenter nature of the latter.…”
Section: Resultsmentioning
confidence: 99%